USING LMS (LEARNING MANAGEMENT SYSTEM) IN ORGANIZING LESSONS IN THE EXAMPLE OF GOOGLE CLASSROOM WHAT IS LMS? - Aykhojayeva Umida Abdumajidovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the advantages, opportunities and achievements of teaching students by using LMS in the organization of lessons in general secondary schools using the example of computer science.